The Structural Model of Corporate Farming in Improving the Welfare of Sugarcane Farmers in Malang Regency - Indah Kumala, Sella Candra; Eri Yusnita Arvianti; Budi Santosa (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2026)
This study aims to analyze the structural model of corporate farming in improving the welfare of sugarcane farmers in Malang Regency. As an agrarian country, Indonesia has great potential in developing sugarcane as a raw material for the sugar industry; however, domestic production has not yet been able to meet national demand. PG Krebet Baru in Malang Regency has implemented a corporate farming model since 2015 through the nucleus-plasma scheme. The study uses a quantitative approach with Structural Equation Modeling based on Partial Least Squares using WarpPLS software. The research sample consisted of 67 partner sugarcane farmers of PG Krebet Baru, selected using the Slovin formula. Data were collected through observation and in-depth interviews using a Likert scale questionnaire.